Analysis of changes in the labour market in Poland in 2009–2018 (Economic and Political Thought, 2020)
The purpose of the article is to identify the situation of workers andidentify factors that affected the situation in the labour market in Poland in2009–2018. The research hypothesis is that the situation in the labour marketin Poland was improving. Research questions, however, are whether and howthe situation of workers, employees, and labour costs per employee and hourworked changed. The report also assesses the information on unemployment,including newly registered and deregistered unemployed, the unemploymentrate and job offers. Based on these data, an analysis of changes in the leveland calculated dynamics of growth is carried out. The statistical data of thelabour market of the Central Statistical Office in Warsaw, published in theStatistical Yearbooks of the Republic of Poland for the years 2009–2018, areused for the analysis and evaluation. The years 2009–2018 are adopted forthe analysis, because this is an important period for Poland as it covers theeconomic development, the economic crisis and the period after the crisis.
Keywords: labour market, employees, employment, unemployment, labour costs